Preparation of magnetic porous graphene for the adsorption of typical sulfonamides - TONG Fanke; GUAN Tong; ZHOU Shuangxi; WANG Wei (Gongye shui chuli)
Novel magnetic porous graphene oxide(GO-TF/Fe3O4) composites were prepared by chemically intercalating porous graphene oxide(GO-TF) with tetrafluoroterephthalonitrile(TF) as a rigid molecular backbone and loading nano-Fe3O4 onto GO-TF by mechanical ball milling. The adsorption performance of magnetic GO-TF/Fe3O4 for sulfadiazine(SD) was investigated by using adsorption kinetic models and isothermal models to study the adsorption rate and adsorption capacity of sulfadiazine(SD) on GO-TF/Fe3O4. Compared to the removal of SD by GO,the adsorption removal performance of GO-TF/Fe3O4 was significantly improved, and the saturation adsorption capacity reached 106.57 mg/g, which indicated that new adsorption pores were formed by the TF-supported GO nanosheets and new adsorption sites were formed by the successful embedding of nano Fe3O4 onto GO-TF after ball milling. The effect of solution pH on the adsorption properties of GO-TF/Fe3O4 was also investigated,and it was found that low pH was favorable for SD adsorption. The adsorption of SD on GO-TF/Fe3O4 mainly involved π-π interactions,hydrogen bonding,and electrostatic interactions. Additionally,GO-TF/Fe3O4 showed good reuse performance for SD within 5 cycles.